2016
DOI: 10.1039/c6cy00761a
|View full text |Cite
|
Sign up to set email alerts
|

Isoprene synthesis from formaldehyde and isobutene over Keggin-type heteropolyacids supported on silica

Abstract: Isoprene synthesis from formaldehyde and isobutene over Keggin-type heteropolyacids supported on silica † V. L. Sushkevich, * a V. V. Ordomsky ab and I. I. Ivanova ac Gas phase Prins condensation of isobutene with formaldehyde has been studied over different Keggin-type heteropolyacids supported on amorphous silica. The catalysts were characterized by elemental analysis, X-ray diffraction, low temperature nitrogen adsorption, TPD of ammonia, FTIR of adsorbed pyridine and NMR spectroscopy. The activity of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 25 publications
2
39
0
Order By: Relevance
“…The olenic carbons are most probably protonated at the acidic sites under high temperature to give working sites as C + . 9,21 Furthermore, the ratio of the two peaks changed slightly with TOS, which meant the coke components changed little, which was much different from this reaction over NbP catalysts. In the induction period, there was lower selectivity due to the insufficient number of working sites of C + because of the low carbon deposition.…”
Section: Study Of the Nature Of The Active Sitesmentioning
confidence: 89%
See 3 more Smart Citations
“…The olenic carbons are most probably protonated at the acidic sites under high temperature to give working sites as C + . 9,21 Furthermore, the ratio of the two peaks changed slightly with TOS, which meant the coke components changed little, which was much different from this reaction over NbP catalysts. In the induction period, there was lower selectivity due to the insufficient number of working sites of C + because of the low carbon deposition.…”
Section: Study Of the Nature Of The Active Sitesmentioning
confidence: 89%
“…16 The earlier route for IP synthesis was based on a two-step reaction: 17 (1) the condensation of IB and formaldehyde to produce 4,4dimethyldioxane-1,3 (DMD) in the liquid phase, and (2) the cracking of DMD into IP over solid catalysts (Scheme 1a). 18 The two-step process has various drawbacks, [19][20][21] and consequently a new promising route is urgently needed. Developing a onestep selective process is a very attractive pathway in this regard on account of its simplied procedures, and due to the possibility of easily manufacturing high purity isoprene (Scheme 1a).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…21,22 Very recently, it was uncovered that the reaction of isobutene and formaldehyde on acid sites leads to the formation of high amounts of carbonaceous deposits on the catalysts. 23 Sushkevich V. L. et al 24 reported a heterogeneous catalyst with 3D ordered carbonaceous framework through the Prins condensation over the solid acid catalysts, the important key of such method is heavily coke deposited on the catalyst in the course of the vapor reaction. Herein, inspired by huge carbonaceous deposition on the acid catalyst, we used phosphorus modied mesoporous silica as template and the impregnated acid could lead to the selective formation of carbon frameworks inside the template mesopores, preventing external carbon deposition.…”
Section: Introductionmentioning
confidence: 99%